Glutamate in Life and Death of Retinal Amacrine Cells* - Duarte, Carlos B. (1998)
1. Glutamate is the neurotransmitter released by bipolar cells at their synapses with amacrine cells. The amacrine cells express ionotropic (NMDA, AMPA and kainate) and metabotropic (mGluR1, mGluR2, mGluR4 and mGluR7) glutamate receptors and may take up glutamate from the synaptic cleft.